Increased authenticity in practical assessment using emergency case OSCE stations - Rüsseler, Miriam; Weinlich, Michael; Byhahn, Christian; Müller, Michael P.; Jünger, Jana; Marzi, Ingo; Walcher, Felix (Advances in health sciences education, 2010)
In case of an emergency, a fast and structured patient management is crucial for patient’s outcome. The competencies needed should be acquired and assessed during medical education. The objective structured clinical examination (OSCE) is a valid and reliable assessment format to evaluate practical skills. However, traditional OSCE stations examine isolated skills or components of a clinical algorithm and thereby lack a valid representation of clinical reality. We developed emergency case OSCE stations (ECOS), where students have to manage complete emergency situations from initial assessment to medical treatment and consideration of further procedures. Our aim was to increase the authenticity and validity in the assessment of students’ capability to cope with emergency patients. 45 students participated in a 10-station OSCE with 6 ECOS and 4 traditional OSCE stations. They were assessed using a case-specific checklist. An inter-station and post-OSCE-questionnaire was completed by each student to evaluate both ECOS and traditional OSCE. In this study, we were able to demonstrate that ECOS are feasible as time-limited OSCE stations. There was a high acceptance on both students and examiners side. They rated ECOS to be more realistic in comparison to the traditional OSCE scenarios. The reliability estimated via Crohnbach’s α for the 6 ECOS is high (0.793). ECOS offer a feasible alternative to the traditional OSCE stations with adequate reliability to assess students’ capabilities to cope with an acute emergency in a realistic encounter.
Gesehen am 23.06.2023